Main aspects of translation competence as an important element of professional training of students - Abduganieva, Djamila; Sultonov, Feruz. (The Lingua Spectrum, 2025)
This article examines the theoretical foundations of translation competence and its models in modern research. The authors emphasize the significance of translation activities in international communication and highlight the need to integrate linguistic, cultural, technological, and professional skills in translator training. The article explores various components of translation competence, including linguistic knowledge, cultural understanding, psychophysiological and strategic skills, as well as the ability to utilize translation technologies. Using approaches such as the PACTE Group model and others, the authors analyze multi-component models of competence and stress the importance of combining theory with practice in translation education. Additionally, the role of metacompetence and its importance in professional growth is discussed. The authors underline that translation competence is a dynamic phenomenon that evolves over time. The article provides theoretical and practical recommendations for improving translation education and emphasizes the need for continuous research and development in this field to meet the demands of an ever-changing professional environment.